2010
DOI: 10.4103/0970-9290.70793
|View full text |Cite
|
Sign up to set email alerts
|

Mucocele - A study of 36 cases

Abstract: We conclude that there was male predominance and they were more affected in 2nd and 3rd decade. The lateral side of lower labial mucosa was the commonest site and the trauma due to teeth or lip biting was the major etiological factor for the occurrence of the mucocele. The article highlights role of psychological stress in occurrence of mucocele. The reader should understand the importance of histopathology examination and should try to control the psychological stress in such mucocele patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
28
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 1 publication
9
28
2
3
Order By: Relevance
“…Large series reported that salivary mucoceles represent 16%-17,2/% of all oral and maxillofacial lesions in pediatric patients [15,16] . Our results showed prevalence (65,68%) in patients aged from 11 to 17 years and are in agreement with previous studies [17,18,19] . Whereas 34,31% of our patients were under the age of 10 years and this fi nding may have some importance in preparing these patients for surgery: younger patients may require additional measures in terms of management/approach, anesthesia and sedation.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Large series reported that salivary mucoceles represent 16%-17,2/% of all oral and maxillofacial lesions in pediatric patients [15,16] . Our results showed prevalence (65,68%) in patients aged from 11 to 17 years and are in agreement with previous studies [17,18,19] . Whereas 34,31% of our patients were under the age of 10 years and this fi nding may have some importance in preparing these patients for surgery: younger patients may require additional measures in terms of management/approach, anesthesia and sedation.…”
Section: Discussionsupporting
confidence: 82%
“…According to the literature [1,13,14,19] salivary mucoceles show female predominance whereas in our study was found a very weak male predilection. However, Jani et al [18] reported a slight male predominance (1:1,2) which is very near to our fi nding. Salivary mucoceles can appear at any site of the oral mucosa where salivary glands are present.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Mucoceles are most often encountered in children and young adults, and the mucosal surface of the lower lip is the favoured site, followed by buccal mucosa, the floor of the mouth, tongue and palate (13,18). In our study, we found that the mucocele is common in males, mostly in a younger age group as 2 nd to 3 rd decade and that the lower labial mucosa is the most common site.…”
Section: Discussionsupporting
confidence: 52%
“…[1] They are cavities that are fi lled with mucus and lined by epithelium. There are two main types of mucocele namely extravasation and retention type.…”
Section: Introductionmentioning
confidence: 99%